Liver X receptor as a drug target for the treatment of breast cancer. Issue 5 (June 2016) - Wu, Ying; Yu, Dan-dan; Yan, Da-li; Hu, Yong; Chen, Dan; Liu, Yun; Zhang, He-da; Yu, Shao-rong; Cao, Hai-xia; Feng, Ji-feng
Abstract : Liver X receptor (LXR) has been exploited widely as a drug target in breast cancer treatment, and various mechanisms underlying the effects of LXR in this area are well studied. The activated LXR plays important roles in estrogen receptor α (ERα) − breast cancer cells, such as reducing cell proliferation and arresting cell cycle progression. Different LXR ligands have diverse effects on the development of breast cancer, such as the inhibitory effect of oxysterol, which can return cells to normocholesterol conditions and target other metabolic genes. Moreover, 27-hydroxycholesterol, a locally produced cholesterol metabolite, reportedly promotes the proliferation of ERα + breast cancer cells in vitro and facilitates tumor metastasis with other LXR ligands. Moreover, the expression of LXR also exerts potential effects on immune surveillance, tumor immunity, and tumor microenvironment. These advances in breast cancer research indicate that LXR may be a new therapeutic target to treat the refractory or drug-resistant subtypes of breast cancer.